(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
A comparative species analysis for divisions and classes in bryofloras of phytogeographical regions of Ukrainian Livoberezhya revealed for Levoberzhne Polissya - 272 species (incl. 3 from Anthocerotophyta, 46 - Marchanthoiphyta and 223 species from Bryophyta), for Levoberzhna Forest-steppe - 229 species (incl. 2 - Anthocerotophyta, 28 - Marchanthoiphyta, 199 - Bryophyta), from Levoberzhna Steppe - 290 (1 - Anthocerotophyta, 31 - Marchanthoiphyta, 258 - Bryophyta). Among 385 species of bryobionta in Ukrainian Levoberzhya, 165 species are common for all three phytogeographical areas, that includes less than a half of the bryoflora species (42.8%). Among them, 1 species from Anthocerotophyta, 17 - Marchanthoiphyta and 147 - Bryophyta. Among Bryophyta, Briopsida dominates - 125 species (upper-sporiferous mosses - 71 species, side-sporiferous mosses - only 54), 13 species of Sphagnopsida and 9 - Polytrichopsida. There are 165 species of bryobionta in all three areas of Ukrainian Livoberezhya, 82 species are found in certain two areas; 138 of 385 species of bryobionta are specific for phytogeographical areas that comprizes 35.8% of the bryoflora of Ukrainian Livoberezhya. Among them, 81 species are found in Levoberezhna Steppe, 42 - Levoberezhne Polissya, and only 15 species - in Levoberezhna Forest-steppe. The Bryoflora Specificity Coefficient (BSC) is offered. Among three Bryofloras studied, the highest meanings of the coefficient are in Levoberezhna Steppe - 21.03, Levoberezhne Polissya - 10.9, the lowest BSC is in Levoberezhna Forest-steppe - only 3.89.